2015
DOI: 10.1111/bph.13260
|View full text |Cite
|
Sign up to set email alerts
|

α7 nicotinic ACh receptor‐deficient mice exhibit sustained attention impairments that are reversed by β2 nicotinic ACh receptor activation

Abstract: BACKGROUND AND PURPOSEDisruptions of executive function, including attentional deficits, are a hallmark of a number of diseases. ACh in the prefrontal cortex regulates attentive behaviour; however, the role of α7 nicotinic ACh receptor (α7nAChR) in attention is contentious. EXPERIMENTAL APPROACHIn order to probe attention, we trained both wild-type and α7nAChR knockout mice on a touch screen-based five-choice serial reaction time task (5-CSRT). Following training procedures, we then tested sustained attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Interference with the cholinergic system can produce fluctuations in attentive engagement in 5CSRTT 45,46 . Analysis of attention performance in distinct temporal phases of 5CSRTT sessions showed that inhibiting cholinergic BF-to-mPFC projections reduced accuracy of responding only during the first half of the session (early trials 0–50), but not the second half of the session (late trials 51–100) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interference with the cholinergic system can produce fluctuations in attentive engagement in 5CSRTT 45,46 . Analysis of attention performance in distinct temporal phases of 5CSRTT sessions showed that inhibiting cholinergic BF-to-mPFC projections reduced accuracy of responding only during the first half of the session (early trials 0–50), but not the second half of the session (late trials 51–100) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interference with the cholinergic system can produce fluctuations in attentive engagement in 5CSRTT 42,43 . Analysis of attention performance in distinct temporal phases of 5CSRTT sessions showed that inhibiting cholinergic BF-to-mPFC projections reduced accuracy of responding only during the first half of the session (early trials 0-50), but not the second half of the session (late trials 51-100) (Fig 5H).…”
Section: Resultsmentioning
confidence: 99%
“…We did not formally calculate power analysis a priori. Typical experiments using the Bussey-Saksida touchscreen technology use samples sizes between 7 and 13 mice per group (Beraldo et al, 2015; Kolisnyk et al, 2015; Kolisnyk et al, 2013; Lim et al, 2019; Romberg et al, 2013b; Romberg et al, 2011). Based on these previous studies, and depending on cohort availability, we assigned a minimum of 10 animals per genotype, sex and site, anticipating some mortality.…”
Section: Methodsmentioning
confidence: 99%